Comparison between gravimetric measurement and visual estimation of postpartum blood loss. (7th June 2011) - Dutton, P J; Vause, S; Samangaya, R A
Abstract : Background: In clinical practice, postpartum blood loss is usually estimated visually. Studies have demonstrated visual estimation of blood loss is inaccurate in comparison to other methods, but little attention has been given to gravimetric measurement (weighing). Objective: To determine the difference between gravimetric measurement of blood loss (MBL) and visual estimation of blood loss (EBL) after delivery. Methods: A prospective study recruited women in labour or having elective caesarean section. Blood-stained items from delivery were weighed, and the total dry weight of items subtracted from total blood-stained weight. Blood weight (g) was converted into blood volume (ml). Results: There were 60 normal vaginal deliveries, 24 instrumental deliveries and 25 caesarean sections (n=109). MBL was significantly higher than EBL in instrumental deliveries (p=0.018, Mann–Whitney) and caesarean sections (p=0.0268, Mann Whitney). There was no significant difference in MBL and EBL in normal vaginal deliveries. Blood loss was underestimated in 75% of women, and overestimated in 23%. In EBL <249 ml median difference to MBL was underestimation of 55 ml (range overestimation 80 ml – underestimation 420 ml). In EBL 250–499 ml median difference to MBL was underestimation of 65 ml (range overestimation 219 ml – underestimation 760 ml). In EBL ≥500 ml median difference to MBL was underestimation of 272 ml (range overestimation 115 ml – underestimation 1375 ml). Conclusions: Gravimetric measurement is economical and easy to perform. It should be employed as an adjunct to visual estimation with blood loss greater than 250 ml, and should be utilised in instrumental deliveries and caesarean sections.